The Impact of Foreign Capitulation on Islamic Sharia in The Ottoman Empire - Meirison Meirison (Faculty of Sharia UIN Kiai Ageng Muhammad Besari Ponorogo, 2020)
The capitulation was initially closer to trade agreements but also related to the rule of law and justice. This article aims to explain how the impact of capitulation on sharia. This foreign capitulation became very detrimental after the Ottoman conquest stagnated. By conducting a literature study and descriptive analysis method, the writer describes and analyses the flood of goods. High taxes for the indigenous population cause a setback in the trading business. Capitulation also had an impact on bringing about the dualism of law and justice. Most Islamic Jurists who practice Hanafi schools believe that a part of hudud and qisas must be applied to non-Muslims in an Islamic state. As happened in Western Europe, the law is linked to the territory without any exceptions, yet the enormous tolerance of the Ottoman Turks has been a factor in its destruction.Kapitulasi pada mulanya lebih dekat kepada perjanjian dagang, akan tetapi terkait juga dengan kedaulatan hukum dan peradilan. Penulisan ini bertujuan untuk menjelaskan bagaimana dampak kapitulasi terhadap syari’ah. kapitulasi asing ini menjadi sangat merugikan setelah penaklukan Turki Usmani mengalami stagnasi. Dengan melakukan studi pustaka dan metode analisis deskriptif penulis menggambarkan dan menganalisis pembanjiran barang, pajak yang tinggi bagi penduduk pribumi menyebabkan kemunduran dalam usaha dagang. Hal ini juga berdampak dalam memunculkan dualisme hukum dan peradilan. Jumhur fuqaha yang bermazhab Hanafi berpendapat sebagian dari hudud dan qisas haruslah diterapkan terhadap non muslim yang berada negara Islam. Seperti yang terjadi di Eropa Barat, yaitu hukum dikaitkan dengan wilayah tanpa ada pengecualian dan tetapi toleransi Turki Usmani yang sangat besar telah menjadi salah satu faktor kehancuran.